Crystallite formation effect on the physicochemical properties of SPEEK membranes for fuel cell application. (8th March 2018) - Troni, Elisabetta; Donnadio, Anna; Pica, Monica; Carbone, Alessandra; Gatto, Irene; Casciola, Mario
Abstract: Crystallite formation in membranes cast from sulfonated poly(etheretherketone) (SPEEK) dispersions in dimethylacetamide has been investigated by differential scanning calorimetry. The crystallites melt at 220 °C and the melting enthalpy (ΔHm ) is strongly influenced by environmental conditions of solvent evaporation. When solvent is evaporated in air, ΔHm decreases with increasing the evaporation temperature so that no crystallites are formed above 45 °C. The study of crystallite formation at 30 °C, under controlled relative humidity (RH) and solvent evaporation rate, has shown that ΔHm decreases i) with decreasing RH from 75% to 5%, at constant evaporation rate, and ii) with increasing evaporation rate, especially at low RH. The exchange of protons with sodium ions results in an increase of the crystallite melting temperature thus indicating the presence of sulfonic groups in the crystallites. In comparison with crystallite-free SPEEK membranes, the presence of crystallites turns out in enhanced membrane mechanical properties, reduced hydration in liquid water above 75 °C, strongly anisotropic swelling (occurring mainly in the through-plane direction) and better performance in H2 /air fuel cell at 70 °C. Graphical abstract: Highlights: SPEEK crystallites were formed under controlled temperature and relative humidity. Mechanical properties of SPEEK membranes improved in the presence of crystallites. Membranes with SPEEK crystallites showed reduced liquid water uptake above 70 °C. Reduced in plane swelling was found for SPEEK crystallite containing membranes. Membrane fuel cell performance improved in the presence of SPEEK crystallites.